Public Goods Provision in the Early Modern Economy Comparative Perspectives from Japan, China, and Europe - Tanimoto, Masayuki; Bin Wong, R. (University of California Press, 2019)
Historically, for sustaining and reproducing their economic lives, people have obtained goods and services through various ways. How did people tackle issues that the market did not handle well? This volume compares early modern efforts to provide "public goods"-defined in contraposition to market-mediated goods and goods provided through personal relations, such as kinship ties. We examine poverty and famine relief, infrastructure building, and forestry management in East Asia and Europe, using Japan's Tokugawa era (1603-1868) as a benchmark from which consider the cases in Prussia, China, and England. Taking advantage of rich scholarship on the role of autonomous village and regional society in Japan's early modern history, the volume highlights the diverse approaches to providing public goods across societies, relativizing the discussion on the formation of fiscal state drawn from the experience in "advanced" Western Europe, and it constructs the beginnings of an early modern basis for forecasting the diversity in public-goods provision future into the modern and contemporary periods.